The role of accounting information in decision-making in small industrial projects: a field study in Najaf Governorate - حسين هادي عنيزة (Iraqi Journal for Administrative Sciences, 2024)
Small projects in general and industrial projects in particular, like others, contribute to the development process and the development of economic and social activity within the general framework of state plans. Economic development means the ability to implement a set of structural changes in society, which achieves a fair distribution of national income, leading to economic and social well-being, and also includes providing good services to citizens, including health, education, housing, culture, transportation, etc. The role of accounting in addressing imbalances in the economic structure is highlighted on the basis that accounting, in its modern concept, is an advanced system for measuring and communicating financial and economic information to decision-makers aimed at developing and improving weak factors to stimulate their participation in the economic development process, by unifying accounting measurement methods for exploiting energies and the interaction of projects with their environment. This unification is based on the unified processing of accounting data, and establishing advanced rules for its operation and methods of displaying and analyzing it, so that it ultimately serves decision-makers of different categories and needs. Small projects have great economic and social importance. It must have the reasons, means or tools that ensure good performance and the best use of available economic resources. There is no doubt that accounting information systems are among the most important and best of these tools, as without them, the continuity and development of these projects cannot be or at least doubted. Financial statements (budget, income statement, statement of changes in financial position and statement of retained earnings) are considered outputs of the accounting system that provide information to its users for the purpose of making decisions. It is expected that the weakness in the accounting information system for small projects results primarily from the lack of integration of its elements or the failure to use modern technology that provides fast and advanced information, but it is seen that these projects refrain from using these elements due to their high costs compared to the profits achieved by these projects. Also, most operations in small projects remain within the scope of personal knowledge and direct control of its owner, who is in most cases its manager as well.